Parallel in-situ measurement of heliostat aim points in central receiver systems by image processing methods. (1st March 2019) - Bern, Gregor; Schöttl, Peter; van Rooyen, De Wet; Heimsath, Anna; Nitz, Peter
Highlights: In-situ aim point measurement plug-in "HelioControl" can be integrated in both new and existing Central Receiver Systems. Direct feedback on true aim points of heliostats in operation is possible. Potential calibration of 7400 heliostats in less than one hour. Abstract: Central Receiver Systems use thousands of heliostats distributed in a field to reflect the solar radiation to a receiver installed at a tower. The large distances between the heliostats and their aim point require a high precision of the heliostat control and drive system to efficiently concentrate the solar radiation and to allow for a safe and reliable plant operation. Precise calibration procedures are needed for the commissioning of open loop systems. Furthermore, the need for cost reduction in the heliostat field motivates for precise and fast calibration systems allowing for savings in the design of the individual heliostats. This work introduces a method for the measurement of true aim points of heliostats in operation. A proposed application is the plug-in system HelioControl, to be used for parallel in-situ calibration of multiple heliostats in operation. The approach aims at extracting the focal spot position of individual heliostats on the receiver domain using image analysis and signal modulation. A centralized remote vision system, installed far from the harsh conditions at the focal area, takes image sequences of the receiver domain. During the measurement, a signal is modulated on different heliostats which is then extracted for the retrieval of the true aim points. This paper describes the theoretical background of the methodology and demonstrates the functionality based on two simulated cases showing the practical advantages introduced with this approach.